A new species of the genus Elasmopus from Miyako Island, Japan (Crustacea: Amphipoda: Maeridae) - Nakamura, Yasuhiro; Nakano, Takafumi; Ota, Yuzo; Tomikawa, Ko (Zootaxa, 2019)
A new species of the maerid amphipod, Elasmopus nkjaf, from Miyako Island, Ryukyu Islands, Japan, is named and described. Additionally, nucleotide sequences of nuclear 28S ribosomal RNA and histone H3 as well as mitochondrial cytochrome c oxidase subunit I and 16S ribosomal RNA from its holotype and paratype were determined. Elasmopus nkjaf sp. nov. belongs to the rapax-group, and distinguished from the other rapax-group species by long setae on ventral margin of epimeral plate 3, gland cone of peduncular article 2 of antenna 2 not reaching to end of peduncular article 3, propodus of gnathopod 1 facially setose, length of propodus of male gnathopod 2 shorter than 3 times as long as length of carpus, medial face of propodus of male gnathopod 2 shallowly hollowed, posterior margin of epimeral plate 3 without denticles. A key to the species of Elasmopus species occurring Japanese and adjacent waters is provided.